2021
DOI: 10.1177/10547738211024884
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 Pandemic on the Lifestyle Behaviors of Individuals

Abstract: The study was planned and administered as a descriptive study to determine how COVID-19 pandemic affected the lifestyle behaviors of individuals. The study was administered from 30 June to 30 September by including 615 adult individuals who had been exposed to the COVID-19 pandemic. Of the healthy lifestyle behaviors scale II, the total mean score was found to be 126.37 ± 18.58. The health responsibility ( p = .032) and nutrition ( p = .004) subscale mean scores of women were found to be significantly higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Participants had an average median HLBS-II score, which has been reported by earlier studies (Devran Enginoğlu et al, 2021;Uysal & Argin, 2021). Uysal and Argin (2021) reported higher "health responsibility," "spiritual development," and "nutrition" scores in women during the pandemic (Uysal & Argin, 2021). Our participants had the highest score on "spiritual development" and the lowest on "physical activity."…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Participants had an average median HLBS-II score, which has been reported by earlier studies (Devran Enginoğlu et al, 2021;Uysal & Argin, 2021). Uysal and Argin (2021) reported higher "health responsibility," "spiritual development," and "nutrition" scores in women during the pandemic (Uysal & Argin, 2021). Our participants had the highest score on "spiritual development" and the lowest on "physical activity."…”
Section: Discussionsupporting
confidence: 84%
“…HLBS-II scores are affected by socioeconomic disparities (Koçoğlu & Akın, 2009). Uysal and Argin (2021) argue that people with a bachelor's or a higher degree and those with a positive income are more likely to have healthy lifestyles (Uysal & Argin, 2021). On the other hand, women and unemployed people have low HLBS-II scores (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 35 (29.5%) studies have examined PA among these groups. Of these, 18 studies reported total PA level have decreased among patients with or without chronic disease(s) (40,43,65,91,123,131,134), diabetes patients (39,86,99,135), COVID-19 patients (21,124,123), heart failure patients (17), multiple sclerosis patients (64), orthopedic patients (118), and adults with pain (55,136). When stratifying across the PA intensity, one study among postmenopausal women had lower levels of PA (68), three other studies reported low MVPA among adults with or without the chronic disease (66) and COVID-19 patients (62,75), and one study reported a decrease in LMVPA among adults with or without the chronic disease (127).…”
Section: Physical Activity Among Adults With Special Considerations A...mentioning
confidence: 99%
“…Similarly, in the relevant literature, there are research studies showing that HPLP-II scores were in general at a low level during the Covid-19 pandemic. 6,12 In the research study conducted by van der Werf et al 15 with Dutch adults, it was put forward that the number of adults adopting a healthy lifestyle was higher than that of adults adopting an unhealthy lifestyle during the Covid-19 pandemic. On the other hand, numerous research studies found that the process of the Covid-19 pandemic led to falls in levels of physical activity and healthy nutrition.…”
Section: Adults' Healthy Lifestyle Behaviorsmentioning
confidence: 99%
“…7 In this respect, finding out individuals' health behaviors during the process of the Covid-19 pandemic is quite important to the identification of the effect of restrictions on individual and societal consequences. 8,9 In the relevant literature, there were research studies that analyzed individuals' health behaviors during the process of the Covid-19 pandemic, [2][3][4]6,[10][11][12][13] however, it was discerned that a limited number of research studies addressed this topic in Turkey.…”
Section: Introductionmentioning
confidence: 99%